Market concentration and producer prices - Huzeyfe Torun; Ahmet Duhan Yassa (Central Bank Review (CBR), 2023)
This study investigates the role of sectoral market structure in the inflationary dynamics of the domestic producer prices (D-PPI) in Türkiye. We start by reporting the fact that industries with intense competition had lower producer price inflation compared to industries with low-competition in the past few years. Further investigation shows that this differentiation across industries corresponds to the years with higher exchange rate volatility. The industries characterized with low-competition have higher annual producer price inflation on average than those that are characterized with high-competition especially during the periods of high exchange rate volatility. Results are robust to a wide set of additional specifications and cast light on the role of market structure on firms' pricing behavior in Türkiye.
Keywords: D4; E31; F31; L11; 330; Competition; Exchange rate pass-through; Inflation; Market concentration; Producer prices